Attitudes, preferences, and intentions of German households concerning participation in peer-to-peer electricity trading - André Hackbarth (Hochschule Reutlingen, ESB Business School, 2018)
Based on a survey among customers of seven German municipal utilities, we estimate hierarchical multiple regression models to identify consumer motivations for participating in P2P electricity trading and develop implications for marketing strategies for this currently relatively unknown product. Our results show a low importance of socio-demographics in explaining differences between consumer groups, but high influence of attitudes, knowledge and likelihood to purchase related products. The most valuable target groups for P2P electricity trading marketing strategies of municipal utilities first and foremost should aim at are innovators, especially prosumers. They are well-informed about and open-minded concerning electricity sharing and highly environmentally aware. They ask for transparency and are willing to purchase related products. They are attracted by the ability to share generation and consumption and to a lesser extent by economic reasons. Our results indicate that the marketing efforts should to a special degree take peer effects into account, as they are found to wield great influence on general openness towards and purchase intention for P2P electricity products. Finally, municipal utilities should build on the high level of satisfaction and trust of consumers and use P2P electricity trading as measure to keep and win customers willing to change their supplier.
urn:nbn:de:bsz:21-dspace-854393
Keywords: 650